USING INTERACTIVE METHODS TO INCREASE THE EFFECTIVENESS OF MUSIC LESSONS (Conferencea, 2022)
This article provides information about the possibilities of using pedagogical technologies in music education, ways of applying advanced pedagogical technologies to music lessons.